Determination of the Pressure Coefficient of Optical Attenuation in Different Layers of In-Vivo Human Skins With Optical Coherence Tomography - Ya Su; X. Steve Yao; Changjiang Wei; Yimin Wang; Hongjie Wang; Zhihong Li (IEEE Photonics Journal)
We use optical coherence tomography (OCT) to systematically study the dependence of the optical attenuation coefficient $μ_{t}$ upon the applied pressure $P$ in different depth regions of the human skin in vivo. We find that the same OCT data can be used to estimate thicknesses of the epidermis layer and the epidermis–dermis junction and obtain the thickness changes in these skin layers induced by the pressure. We further propose and demonstrate using the correlation map to identify depth regions in which $μ_{t} $ has positive and negative correlations with the applied pressure and study in detail the changes of $μ_{t} $ in dermis with the applied pressure. By using a low-cost thin-film pressure sensor to monitor the applied pressure accurately, we are able to quantitatively obtain the pressure dependence of $μ_{t} $ in different skin layers in vivo with the following interesting findings: When a pressure ranging from 0 to 20 kPa is applied on the volar side of the forearm skin, $μ_{t} $ increases with the applied pressure in the epidermis layer, which coincides with the thickness decrease and increase of the epidermis and the epidermis–dermis junction, respectively. In contrast, $μ_{t} $ decreases with applied pressure in the upper dermis but increases again in the deeper dermis with applied pressure. Our results demonstrate that the OCT correlation map and the thin-film sensor are effective tools to study the optical scattering properties of human skin under pressure. We anticipate that our experimental and analytical methods reported in this paper can be useful for clinical diagnostic applications, such as noninvasive blood glucose monitoring.